Kelp Forests: Catastrophes, Resilience, and Management - Wilman, Elizabeth A. (Frontiers in Ecology and Evolution, 2021)
Resilient kelp forests provide foundation habitat for marine ecosystems and are indicators of the ecosystems’ sustainable natural capital. Loss of resilience and imperfectly reversible catastrophic shifts from kelp forests to urchin barrens, due to pollution or loss of a top predator, are part of an ecological tipping point phenomenon, and involve a loss in sustainable natural capital. Management controls to prevent or reverse these shifts and losses are classified in a number of ways. Systemic controls eliminate the cause of the problem. Symptomatic controls use leverage points for more direct control of the populations affected, urchin harvesting or culling, or kelp enhancement. There is a distinction between ongoing structural (press) controls versus temporary perturbation (pulse) controls, and one between shift preventing versus shift reversing/restorative controls. Adaptive management and the real options approach both focus on reductions in uncertainty and control policies with the flexibility to take advantage of those reductions. The various management distinctions are most easily understood by modelling the predator-urchin-kelp marine ecosystem. This paper develops a mathematical model of the ecosystem that is recursively decoupled from the top down and has the potential for two different catastrophic shifts between equilibria. Pulse disturbances, originating from exogenous abiotic factors or population dynamics elsewhere in the metacommunity, can activate shifts. With a flexible piece-wise uniform probability density function for displacements from pulse disturbances, a measure of probabilistic resilience is developed and used as part of an assessment of the ecosystem’s sustainable stock of natural capital. With displacement outcomes clustered around the originating equilibrium, hysteresis is activated, resulting imperfect reversibility of catastrophic shifts, and a loss in natural capital. The difficulty of reversing a shift from kelp forest to urchin barren, with an associated loss in sustainable natural capital, is an example. Management controls are modelled. Systemic and symptomatic, and press and pulse, controls can be complementary. Restorative controls tend to be more difficult/costly than preventative ones. Adaptive management, favoring flexible preventative controls, is shown to create real option value, lowering control costs and/or losses in sustainable natural capital. Two cases are used to illustrate, Tasmania, Australia and Haida Gwaii, Canada.